Perlindungan Hukum terhadap Hak Cipta Lagu Cover Song di Era Digital: Perspektif Undang-Undang Hak Cipta - Weslly Anjeli Sianipar; Lenny Husna (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2026)
This study aims to analyze the forms of legal protection for copyright in cover songs in the digital era based on Law Number 28 of 2014 on Copyright, as well as to assess the effectiveness of its implementation. This research employs normative legal research with a qualitative approach, using statutory, conceptual, and case approaches. The primary legal materials consist of copyright-related legislation, while secondary materials include legal literature and scholarly journals. The findings indicate that the Copyright Law has normatively provided protection through civil, criminal, and administrative mechanisms; however, its implementation remains constrained by structural, cultural, and technological challenges. Therefore, strengthening law enforcement, optimizing digital licensing systems, and enhancing the active role of digital platforms are essential to ensure fair and sustainable copyright protection.